(untitled) (The Review of Diabetic Studies, 2024)
The rapidly aging global population presents substantial challenges for healthcare systems worldwide, necessitating specialized nursing interventions to promote health, maintain independence, and enhance quality of life among elderly individuals. This comprehensive review examines the multifaceted role of nurses in delivering healthcare to elderly populations across diverse settings including community-based programs, long-term care facilities, and acute care environments. The nursing role encompasses comprehensive assessment, care coordination, medication management, health promotion, fall prevention, rehabilitation support, and psychosocial care. Evidence demonstrates that nurse-led interventions significantly improve health outcomes, reduce hospital readmissions, enhance quality of life, and promote healthy aging among elderly patients. Through holistic, person-centered approaches, nurses address the complex physical, cognitive, emotional, and social needs of older adults while advocating for their autonomy and dignity. This review synthesizes current evidence on nursing strategies, challenges, and outcomes in elderly care, emphasizing the critical importance of specialized geriatric nursing education, interdisciplinary collaboration, and evidence-based practice in optimizing healthcare delivery for the aging population. The findings underscore that nurses are essential to achieving sustainable, cost-effective elderly healthcare that honors the preferences and goals of older adults.